Legal Reconstruction of Partnership Agreements in the Oil Palm Plantation Revitalization Program - Firman Saputra; Herman Bakir (Syntax Corporation Indonesia, 2024)
This research discusses the challenges and weaknesses in partnership agreements between PT. Boswa Megalopolis and the community of Aceh Jaya Regency, focusing on aspects of power imbalance, unclear provisions, and minimal legal protection for plasma farmers. Through an analysis of contributing factors such as social and economic structures, availability of information, and the limited role of the government, the need for regulatory reform and practical guidelines is identified to improve justice in partnerships. Furthermore, strengthening mediation institutions and implementing community-based partnership models are proposed as strategies to create sustainable partnerships. These findings are expected to provide insights for policymakers and stakeholders in creating a more just and sustainable partnership system in the oil palm plantation sector.